MODEL NUMERIK 2-D (LATERAL & LONGITUDINAL) SEBARAN POLUTAN CADMIUM(Cd) DI MUARA SUNGAI (STUDI KASUS: MUARA SUNGAI BABON, SEMARANG) - Badrus Zaman; Syafrudin Syafrudin (Universitas Diponegoro, 2007)
Estuary of River Babon very influenced by condition around its drainage basin. estuary of River Babon also have function as a channel of waste disposal from Terboyo Industrial Park, Semarang ( KITS). Cadmium ( Cd) as one of heavy metal pollutant and conservative element will certainly spread at estuarine. Based on research at the time of measurement, known that by the content of Cd at estuary of river Babon equal to ( 0,009 - 0,017) mg / l, where the concentration have exceeded the Quality of Water Go out to sea for the Biota of Go out to sea that is equal to 0.001 mg / l (Kep Men LH No. 51 tahun 2004). Study about disseminating polutan at estuarine can be conducted by using model because by using model can be knowable how disseminating polutan accurately, quickly and cheap so that picture from the model can be made basis for furthermore management. Model developed with numerical 2-D model ( lateral & longitude). Model developed by using equation on the basis of hydrodynamics process and conservative transpor polutan. The equation finished by numerik by using differential method ( finite difference). The result from developed model for the time of t = 1 hour obtained value with 3.028% mistake from field data.